2003
DOI: 10.1242/jeb.00478
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion measurements on the attachment devices of the jumping spiderEvarcha arcuata

Abstract: SUMMARYThe feet of the jumping spider Evarcha arcuata attach to rough substrates using tarsal claws. On smooth surfaces, however, attachment is achieved by means of a claw tuft, the scopula. All eight feet bear a tarsal scopula, which is equipped with setae, these again being covered by numerous setules. In E. arcuata, an estimated 624 000 setules, with a mean contact area of 1.7×105 nm2, are present. The spider's entire contact area thus totals 1.06×1011nm2. Adhesion to the substrate does not depend on the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 34 publications
2
95
0
1
Order By: Relevance
“…The feet of the jumping spider Evarcha arcuata attach to smooth surfaces by means of a claw tuft, the scopula, which is equipped with setae, these again being covered by numerous setules. It was found that a single setule can produce an adhesive force of 38 nN perpendicular to a surface [977]. Multiplying this with the number of setae and comparing it to the mean body weight, a safety factor of 160 is achieved.…”
Section: Cell and Animal Adhesionmentioning
confidence: 99%
“…The feet of the jumping spider Evarcha arcuata attach to smooth surfaces by means of a claw tuft, the scopula, which is equipped with setae, these again being covered by numerous setules. It was found that a single setule can produce an adhesive force of 38 nN perpendicular to a surface [977]. Multiplying this with the number of setae and comparing it to the mean body weight, a safety factor of 160 is achieved.…”
Section: Cell and Animal Adhesionmentioning
confidence: 99%
“…Recent developments in experimental techniques to measure adhesive forces at the level of individual setae (Autumn et al, 2000 and spatulae (Kesel et al, 2003;Langer et al, 2004;Huber et al, 2005) are calling for more systematic theoretical and experimental studies of adhesion mechanisms in biology. A systematic study of biological adhesion mechanisms should be of interest not only to the understanding of biological systems but also to the development of novel adhesive materials or devices for engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…A number of biological studies (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) have found that arrays of setae are a common feature on the adhesion surfaces of many lizards and insects. In the biological literature, the shape, dimensions, and composition of setae from various species are described (1)(2)(3)(4)(5)(9)(10)(11)(12)(13)(14)(15)(16). Also, the mechanical properties and adhesion force of a single gecko seta (7) and even a single spatula (17,18) were the subjects of recent investigations.…”
mentioning
confidence: 99%